Top-cited articles of the last 30 years (1985–2014) in otolaryngology – head and neck surgery. Issue 2 (20th November 2015) - Lenzi, R; Fortunato, S; Muscatello, L
Abstract: Background: The frequency with which a scientific article is cited by other studies is one way to measure its academic influence. Methods: A comprehensive search was performed to identify journal articles in the otorhinolaryngology subject category of the 2013 Journal Citation Report Science Edition over the last 30 years (1985–2014). The 100 most cited articles were reviewed and basic information including the publication year, country of origin, source journal, article type and research field was collected. Results: The 100 most cited articles were published in 15 of the 44 otorhinolaryngology journals. The number of citations per article ranged between 208 and 1559. The leading research field was otology and neurotology ( n = 50), followed by rhinology ( n = 23) and head and neck surgery ( n = 11). Most papers originated in the USA ( n = 64). Conclusion: The possibility of an article being cited is influenced by the publication language, country of origin and source journal.